Magnitude and associated factors of adverse perinatal outcomes among women with oligohydramnios at 3rd trimester at University of Gondar comprehensive specialized hospital, North West Ethiopia - Molla, Mezigebu; Mengistu, Zelalem; Tsehaye, Winta; Sisay, Getasew (Frontiers in Global Women's Health, 2023)
Background Oligohydramnios is a pregnancy condition characterized by low volume of amniotic fluid. Based on ultrasound measurement, it is defined as a single maximum vertical pocket of liquor less than 2 cm or summation of four quadrants vertical pockets of liquor measurement less than 5 cm. It is associated with multiple adverse perinatal outcomes (APO) and complicates 0.5%–5% of pregnancies. Objective To assess magnitude and associated factors of adverse perinatal outcome among women with oligohydramnios at 3rd trimester at University of Gondar Comprehensive Specialized Hospital, North West Ethiopia Methods Institution based cross-sectional study was employed from April 1 to September 30, 2021 in which 264 participants were involved. All women with oligohydramnios at 3rd trimester who meet the inclusion criteria were included. Semi- structured questionnaire was used for data collection after Pre-tested. Collected data was checked for completeness; clarity then coded and entered using Epi data version 4.6.0.2 then exported to STATA version 14.1 for analysis. Result The magnitude of APO was 46.6% (95%CI: 40.5–52.7%). Null parity [AOR = 2.2, 95%CI (1.2–4.2)], presence of hypertensive disorders of pregnancy (HDP) [AOR = 4.9, 95%CI (2.0–12.1)] and presence of intrauterine growth restriction (IUGR) [AOR = 8.4, 95%CI (3.5–20.2)] were found to be predictors of APO. Conclusion Third trimester oligohydramnios is associated with APO. The presence of HDP, IUGR and being nulliparous were predictors of APO.